A replacement name for Faecula Fibiger, 2008 (Lepidoptera: Noctuoidea: Micronoctuidae) - Fibiger, Michael (Zootaxa, 2008)
The genus name Faecula Fibiger, 2008 must be replaced by Faeculoides nom. nov. because Faecula Fibiger, 2008 is preoccupied by Faecula Slipinski & Lawrence, 1997, an Australian coleopteran genus. The genus Faeculoides comprises three species: type species Faeculoides bifusa (Fibiger, 2008), new combination; Faeculoides plumbifusa (Hampson, 1907), new combination; and Faeculoides leucopis (Hampson, 1907), new combination.